Comment on “The Marxist philosophical basis of socialist literature and art” - Mei, YanLing (2023)
Reference to the commented article: LIU, Zijie. The Marxist philosophical basis of socialist literature and art. Trans/Form/Ação: Unesp Journal of Philosophy, v. 46, n. 3, p. 255- 274, 2023.